1992
DOI: 10.1161/01.cir.86.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transient linking of atrial excitation during atrial fibrillation in humans.

Abstract: BACKGROUND Atrial fibrillation is usually thought of as a "random" pattern of circulating wavelets. However, local atrial activation should be influenced by the constant anatomy and receding tail of refractoriness from the previous activation. The general tendency for wave fronts to follow paths of previous excitation has been termed "linking." We examined intra-atrial electrograms recorded during atrial fibrillation for evidence of linking. METHODS AND RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
93
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 20 publications
10
93
0
Order By: Relevance
“…1 However, recent studies have shown organization in AF, 4,5 and others have shown shorter cycle lengths in the LA than in the RA. 9 -12 Moreover, studies from our laboratory demonstrated spatiotemporal organization in AF.…”
Section: Organization and Hierarchy Of Frequencies In Afmentioning
confidence: 96%
See 1 more Smart Citation
“…1 However, recent studies have shown organization in AF, 4,5 and others have shown shorter cycle lengths in the LA than in the RA. 9 -12 Moreover, studies from our laboratory demonstrated spatiotemporal organization in AF.…”
Section: Organization and Hierarchy Of Frequencies In Afmentioning
confidence: 96%
“…[1][2][3] However, recent studies have shown various degrees of organization in AF. 4,5 In addition, studies from our laboratory demonstrated spatiotemporal organization during AF, mainly in the left atrium (LA). 6 -8 Also, animal and human studies have shown that activity during AF is more rapid in the LA than in the right atrium (RA).…”
mentioning
confidence: 99%
“…Part of the reason for this incomplete understanding is the difficulty in obtaining accurate human maps of spatio-temporally varying electrical activity in AF, and hence explaining consistent spatial gradients in rate and dominant frequency 2 and electrical propagation. 3 High resolution mapping techniques, especially ones using optical dyes, have proven to be instrumental in determining the spatio-temporal wave organization in animal models and in explanted human hearts. 4,5 Such models have shown that spatiotemporally variable AF may actually result from periodic sources in the form of spiral waves (electrical rotors) 6,7 or focal sources, in which activation spreads from an origin, 8 that are localized yet lie in unpredictable locations and thus are ideally identified using a wide field of view.…”
Section: Introductionmentioning
confidence: 99%
“…Although previously thought to be a "random" arrhythmia, animal and human studies have shown various degrees of spatiotemporal organization during sustained AF. [1][2][3][4][5][6] In humans, Haissaguerre and colleagues 7 showed that the onset of AF is frequently triggered by atrial premature beats that originate from sleeves of atrial muscle that extend into the pulmonary veins (PVs). Others have reported focal firing within the PVs during sustained AF.…”
mentioning
confidence: 99%